Fortified Cold-Pressed Oils: The Effect on Sensory Quality and Functional Properties - Alexandra Tauferova; Dani Dordevic; Simona Jancikova; Bohuslava Tremlova; Piotr Kulawik (Separations, 2021)
The aim of this study was to monitor sensory quality, stability, selected nutritionally interesting properties and their changes in cold-pressed oil blends after fortification with chia and sesame seeds and seed oils during repeated thermal treatments. Rapeseed (cv. Sidney) and sunflower (cv. Velox) seeds from the Czech Republic were used to produce cold-pressed oils, which were fortified with chia and sesame seeds and seed oils in the concentrations of 1% and 5%. In all oil blends, sensory evaluation (quantitative descriptive analysis and hedonic analysis) and chemical analyses (oxidation degree, hydrolytic stability, chlorophyll and carotenoid content) were carried out in order to perform separation of samples degraded by thermal treatment. Assessors representing consumers were able to differentiate between individual thermal treatments from the viewpoint of pleasantness. Interestingly, the overall pleasantness of all fortified oil samples was still acceptable until the second thermal treatment. On the other hand, the results of the study emphasized the problematic oxidation degree of cold-pressed oil blends. The fortification of cold-pressed oils with chia and sesame seeds and oils did not unambiguously lead to better stability during thermal treatment. The application of elevated temperatures during the culinary use of these types of products should be limited to only one thermal treatment since sensory and chemical changes occur after repeated heating.